Performance Analysis of HC-SR04 and JSN-SRT04T Sensors for Optimization of Microcontroller-based Septic Tank Volume Monitoring Tools - Khakim, Lukmanul; Budihartono, Eko (Publisher Cv. Inara, 2025)
A septic tank is a temporary storage place for household waste, in which there are several gases that if the concentration increases, it will cause several impacts on the health and safety of people or the community around the septic tank. Previous research related to monitoring and neutralizing gas sewers in septic tanks has been successfully made, but the tool has shortcomings in terms of the use of the HC-SR04 sensor, where if the sensor is in humid conditions for a long time, then its performance cannot be optimal, due to the influence of humid space, therefore it is necessary to optimize the tool in terms of detecting the level of fulfillment of septic tank volume. As a result of optimizing the septic tank volume detection sensor which was replaced with the JSN-SR04T sensor, the volume detection results are more accurate and more stable, this is because the JSN sensor is waterproof, so that intervention from a humid environment is minimized. Testing from the two sensors found that the accuracy level of HC-SR04 in measuring distances between 20 to 200 cm, with 12 tests, the accuracy level of JSN-SR04T was 100%, and HC-SR04 was 90.1%.